Glaucoma Screening in Family Members of Glaucoma Patients at a Tertiary Eye Hospital in Eastern Region of Nepal - Bhandari, Ravi Dhar; Khanal, Bandana; Poudel, Manish; Shrestha, Mohan Krishna; Thapa, Suman Shamsher (Nepalese Journal of Ophthalmology, 2021)
Introduction: The second most common cause of blindness in the world is glaucoma. Family history plays an important role in early detection and management of patients with glaucoma. The main objective of this study was to determine the prevalence of glaucoma in first degree relatives of Primary open angle glaucoma (POAG) and Primary angle closure glaucoma (PACG) patients. Glaucoma awareness among the first degree relatives was also assessed. Materials and methods: A cross sectional hospital based study was designed to examine and diagnose glaucoma among first degree relatives of patients with POAG and PACG, attending the outpatient department at Ramlal Golchha Eye Hospital in the Eastern region of Nepal from June 2016 to May 2017. A comprehensive eye examination was conducted by a glaucoma specialist at the hospital. All subjects underwent vision screening, refraction, slit lamp biomicroscopy, intraocular pressure (IOP) measurement, gonioscopy and a dilated fundus examination. All glaucoma suspects and those diagnosed with glaucoma were enrolled for visual field examination. Results: Two hundred and twenty-seven first degree relatives of 72 patients were invited for the examination. Out of 227 individuals, 131 (males 67.94%, females 32.06%) agreed to participate in the study. A total of 23 (17.56%) individuals were diagnosed with glaucoma, 10 (43.47%) as POAG and 13 (56.52%) as PACG. Fourteen percent of parents, 22% of siblings and 9% of off-springs had open angle glaucoma. Among 13 PACG participants, 26.08% of parents, 26.08% of siblings and 4.34% of off-springs had angle closure glaucoma. Awareness among first degree relatives diagnosed with glaucoma was 21.74%. Conclusion: The prevalence of glaucoma among first degree relatives of glaucoma patients was higher than individuals without family history of glaucoma. Promoting awareness on glaucoma and the timely screening of family members can lead to early detection and prevention of blindness from the disease.